2007
DOI: 10.1103/physreve.75.036106
|View full text |Cite
|
Sign up to set email alerts
|

Geographical networks evolving with an optimal policy

Abstract: In this article we propose a growing network model based on an optimal policy involving both topological and geographical measures. In this model, at each time step, a node, having randomly assigned coordinates in a 1x1 square, is added and connected to a previously existing node i, which minimizes the quantity ri2/kialpha, where ri is the geographical distance, ki the degree, and alpha a free parameter. The degree distribution obeys a power-law form when alpha=1, and an exponential form when alpha=0. When alp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 48 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…On the other hand, if removals of facilities are allowed in addition, the upper points move to the lower part, making the scaling law D ∼ ρ α more visible. The difference in results comes from the presence of regulating processes such as removal or relocation, which are also shown in other studies of optimal networks (11,14,15).…”
Section: Summary and Discussionmentioning
confidence: 81%
“…On the other hand, if removals of facilities are allowed in addition, the upper points move to the lower part, making the scaling law D ∼ ρ α more visible. The difference in results comes from the presence of regulating processes such as removal or relocation, which are also shown in other studies of optimal networks (11,14,15).…”
Section: Summary and Discussionmentioning
confidence: 81%
“…In the spatial or geographical networks [33,34], the cost of establishing long-range connections between distant spots is usually higher than the cost of establishing short-range connections. This is clear for railway network, where establishing a long-range connection is obviously expensive because long channels need a larger infrastructure.…”
Section: The Geographical Constraint Of Networkmentioning
confidence: 99%
“…What are the key factors that lead the cortical networks to small-world graphs? Some recent works have demonstrated that the spatially preferential attachment mechanism plays a major role in determining the network evolution [15][16][17][18]. Since these models embrace the topologically preferential attachment introduced by Barabsi and Albert [19], it would result in the fact that the nodes added to the network in the early time have larger probability to become the highly connected ones.…”
Section: Introductionmentioning
confidence: 99%